The economics of an alternative bio-energy feedstock – the case of Jatropha curcas - Tee, Meng Y. (Kansas State University, 2009)
Biofuels such as ethanol and biodiesel are looked upon as the future source of alternative energy. These biofuels will supplement the needs of the ever increasing demand for fuel. Bio-energy feedstock is in high demand and current bio-crude oil prices such as soybeans and palm oil are higher than fossil fuel crude oil prices. Unless the price of fossil fuel crude oil increases beyond that, it would not be economically viable to produce biofuels from these feedstock. Jatropha curcas has been touted as the future of biodiesel. The seeds from the Jatropha curcas are crushed and processed using transesterification. The product of the chemical reaction results in bio-oil and glycerin. The objective of this paper is to study the economics of Jatropha curcas as an alternative bio-energy feedstock. Comparisons are done on Jatropha curcas oil, soybean oil, and palm oil. The Jatropha curcas industry is at its infancy, and crude Jatropha curcas oil is either not available in the open market or extremely difficult to find in any significant amount. However, soybean oil and crude palm oil are traded commodities and their prices are dependent on their demand and supply pressures. Given these conditions, the approach adopted here involved the establishment of a vertically integrated company that grows and harvests the Jatropha curcas feedstock and crushes the seeds to obtain the crude oil, and finally processes it to obtain biodiesel and glycerin. The financial analysis provided results that indicate that the Jatropha curcas has the potential to be a successful feedstock. The conclusion after conducting net present value comparisons shows that the price per kilogram of the Jatropha curcas seed would be the determining factor in the success of this bio-fuel feedstock. As more work goes into the genetic selection of Jatropha curcas for high yield varieties, the feedstock’s potential increases and its potential as a solution to the search for the competitive sources of biodiesel becomes more real.
Keywords: Biofuel; Jatropha curcas; Net Present Value; Palm oil; Soybean oil; Economics, Agricultural (0503); Economics, General (0501); Energy (0791)